2021
DOI: 10.1186/s40001-021-00498-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of structure indicators influencing 3-h and 6-h compliance with the surviving sepsis campaign guidelines in China: a systematic review

Abstract: Background Compliance with the surviving sepsis campaign (SSC) guidelines (Cssc) is a key factor affecting the effects of sepsis treatment. We designed this study to investigate the relationships of the structure indicators of ICU on 3 and 6-h Cssc in China. Methods A total of 1854 hospitals were enrolled in a survey, led by the China National Critical Care Quality Control Center (China-NCCQC) from January 1, 2018, through December 31, 2018. We inv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Quality control construction is an important means to improve the level of diagnosis and treatment in ICU 10 , 11 . Our previous studies shown that quality indicators influencing compliance with the surviving sepsis campaign guidelines in China are the predicted mortality rate and the standardized mortality rate 12 , deep vein thrombosis prophylaxis rate, unplanned extubation rate, reintubation rate within 48 h, and rate of unplanned ICU admission 13 . The compliance with the surviving sepsis campaign guidelines in tertiary hospitals was significantly higher than in secondary hospitals 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Quality control construction is an important means to improve the level of diagnosis and treatment in ICU 10 , 11 . Our previous studies shown that quality indicators influencing compliance with the surviving sepsis campaign guidelines in China are the predicted mortality rate and the standardized mortality rate 12 , deep vein thrombosis prophylaxis rate, unplanned extubation rate, reintubation rate within 48 h, and rate of unplanned ICU admission 13 . The compliance with the surviving sepsis campaign guidelines in tertiary hospitals was significantly higher than in secondary hospitals 14 .…”
Section: Discussionmentioning
confidence: 99%